2021
DOI: 10.1111/pbi.13599
|View full text |Cite
|
Sign up to set email alerts
|

The miR164‐GhCUC2‐GhBRC1 module regulates plant architecture through abscisic acid in cotton

Abstract: Summary Branching determines cotton architecture and production, but the underlying regulatory mechanisms remain unclear. Here, we report that the miR164‐GhCUC2 (CUP‐SHAPED COTYLEDON2) module regulates lateral shoot development in cotton and Arabidopsis. We generated OE‐GhCUC2m (overexpression GhCUC2m) and STTM164 (short tandem target mimic RNA of miR164) lines in cotton and heterologous expression lines for gh‐miR164, GhCUC2 and GhCUC2m in Arabidopsis to study the mechanisms controlling lateral branching. GhC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 61 publications
(79 reference statements)
0
38
0
Order By: Relevance
“…The miR164-CUC module seems conserved in other plant species and in cotton (Gossypium hirsutum) gh-miR164 and gh-CUC2 form a regulatory gene network with BRANCHED 1 (BRC1) that is believed to control branching. BRC1 encodes a TF that controls branching in several plant species [60,61] and it is part of a GRN controlling dormancy and budbreak in apple [5]. Therefore, the downregulation of mdm-miR164c that we observed at ecodormancy (stage 4) (Table 2 and Figure 2C) could be involved in a BRC1-mediated mechanism of budbreak control in apple.…”
Section: Potential Roles Of Target Genes Of De-mirnas During Bud Dormancy Of Applementioning
confidence: 77%
“…The miR164-CUC module seems conserved in other plant species and in cotton (Gossypium hirsutum) gh-miR164 and gh-CUC2 form a regulatory gene network with BRANCHED 1 (BRC1) that is believed to control branching. BRC1 encodes a TF that controls branching in several plant species [60,61] and it is part of a GRN controlling dormancy and budbreak in apple [5]. Therefore, the downregulation of mdm-miR164c that we observed at ecodormancy (stage 4) (Table 2 and Figure 2C) could be involved in a BRC1-mediated mechanism of budbreak control in apple.…”
Section: Potential Roles Of Target Genes Of De-mirnas During Bud Dormancy Of Applementioning
confidence: 77%
“…ABA is essential for dormancy and plays a vital role in regulating bud outgrowth for the red to far-red light (R: FR) [ 21 , 45 ]. González-Grandío et al and Zhang et al revealed that ABA signalling plays a negative role in branching downstream of BRC1 [ 15 , 46 ]. Holalu et al showed that ABA accumulation in axillary buds works downstream of PIF for shade avoidance responses [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, miR164 targets a subset of the NAC genes, including CUP-SHAPED COTYLEDON (CUC) genes that are important for a wide range of meristem-related developmental processes. Recent studies performed in cotton and in the heterologous Arabidopsis system suggest that repression of CUC2 by miR164 is important for branch outgrowth (Zhan et al, 2021). Specifically, CUC2 interaction with BRC1 may modulate ABA levels to control bud growth (Zhan et al, 2021).…”
Section: Extending Our Knowledge Of Conserved Mirnas and Their Regulation Of Axillary Bud Outgrowth To Rosebushmentioning
confidence: 99%